Pax Americana: Gospodarcze podstawy, interesy i przewidywane tendencje (Politeja, 2015)
Pax Americana. The economic bases, interests and projected trendsThe subject of the article is an analysis of economic basis of Pax Americana in the prospect of 10‑20 years. The main factors of geopolitical power are: wealth – entire and per capita, production of leading goods and innovations. An analysis of the position different countries in the advancement of the new economy (knowledge based economy) prove that in the next 20 years USA will be most important power of the west world. Changes on world market of energy will cause changes in defining national interest of USA.